Effect of preferential solvation of polymer chains on vapor-pressure osmometry results: Computer simulation study. Issue 3 (3rd April 2018) - Svoboda, Martin; Lísal, Martin; Limpouchová, Zuzana; Procházka, Karel
ABSTRACT: Preferential solvation of polymer chains by molecules of the thermodynamically better component of the solvent mixture is a general phenomenon which affects properties of dissolved chains and has to be taken into account in the interpretation of results of methods for analysis and characterization of polymers. We have investigated (i) the effect of preferential solvation on vapor-pressure osmometry results in mixed solvents close to θ -conditions and (ii) the danger of formation of associates by coarse-grained computer simulations. The study shows that both effects are negligible and the measurements in mixed solvents can be safely performed.